PATH-60. PRIMARY CNS LYMPHOMA PRECEDED BY ACUTE DEMYELINATION. (11th November 2019) - Low, Justin; Buckley, Anne; Randazzo, Dina
Abstract: Primary CNS lymphoma commonly presents with nonspecific encephalopathy or focal neurologic deficits. Magnetic resonance imaging typically shows a homogeneously enhancing mass with surrounding edema. The imaging differential diagnosis is broad, and includes high grade glioma and neuroinflammatory conditions. Definitive diagnosis therefore requires biopsy. Here we present a case of primary CNS lymphoma that was diagnosed as an acute demyelinating process on initial biopsy. A 68 year old female presented with gait instability and vertigo. MRI showed right cerebellar and right trigonal enhancing lesions. Biopsy revealed an acute demyelinating inflammatory process and she was diagnosed with acute disseminated encephalomyelitis. She was treated with intravenous methylprednisolone followed by oral prednisone with resulting clinical and radiographic improvement. She was re-admitted to hospital 4 months later with encephalopathy. Imaging showed a new enhancing mass in the pericallosal frontal lobes. Repeat brain biopsy showed diffuse large B-cell lymphoma. This case illustrates a highly unusual situation of biopsy-proven central demyelination preceding a primary CNS lymphoma diagnosis. It raises a number of etiopathological questions concerning the coexistence and potential causal relationships between demyelination and lymphoma. Additionally, it highlights the need for repeat biopsy if clinical and radiographic suspicion for lymphoma persists despite an alternative initial biopsy result.